Miejsca obrzędowe ludności kultury łużyckiej i kultury przeworskiej na Kujawach. Część I. Przegląd źródeł - Cofta-Broniewska, Aleksandra (Folia Praehistorica Posnaniensia, 2018)
The article is aimed at presentation of archaeological evidence from Kujavia in relation to reconstruction of religious sphere of the Lusatian and Przeworsk culture communities. In particular, the article explores various features along with their cultural and functional context as well as their natural environment. They are significantly supplemented by accompanying artifacts, which shed some light onto the past customs. Presented cultural facts refer both to the earthly life as well as to the posthumous existence. Additionally, available archaeological evidence contributes to better understanding of various rules responsible for selection of the sacred places and their layout as well as use of various ritual norms in the consecutive periods. The available evidence contributes also to the recognition of the far-reaching contacts between local communities and foreign groups and their mutual relationships.